Experimental investigation of the failure mechanism of 18650 lithium-ion batteries due to shock and drop. (November 2021) - Spielbauer, Markus; Berg, Philipp; Soellner, Jonas; Peters, Julia; Schaeufl, Florian; Rosenmüller, Christian; Bohlen, Oliver; Jossen, Andreas
Abstract: This work presents an experimental investigation of the failure mechanism of 18650 lithium-ion batteries subject to dynamic mechanical loads and the implications of severe damages on the safety function of the current interruptive device (CID), as current literature offers no insight in this topic. First, a conducted shock test series with loads beyond automotive standards showed no distinct impact on various modern cell types in impedance and computed tomography (CT) analysis, while older cell types exhibited signs of damage such as mandrel displacement and increase of ohmic resistance, as had already been reported in literature. A following investigation with acceleration measurements of drops of power tool battery modules revealed that accelerations in some applications can exceed even high load-level standards significantly. In a subsequent test series with axial drop tests in both orientations with various cell types, impact surfaces and states of charge (SOC), multiple cell types exhibited high ohmic failure without a thermal event. Computed Tomography (CT) and Post Mortem analysis revealed that, among various observable damage mechanisms, the predominant failure mechanism is contact loss in the CID region. Even severe mechanical damages, although influencing electrical and thermal behavior, showed no impact on the functionality of the CID in overcharge tests Highlights: Conducted half-sine shock tests beyond automotive standards showed little impact on modern cells. Acceleration measurements in a high load use case showed significantly higher accelerations than in commonly used standards. Repeated drop tests were conducted, and failure mechanisms were evaluated by Computed Tomography (CT) and Post Mortem analysis. The tests indicated primarily high ohmic cell failure due to contact loss in the current interruptive device CID region. Even severe drop induced damages of the CID showed no impact on its functionality in overcharge tests.